Dialectical perspective and treatment in poetry of Khalil Hawi - محمد راضي شارف (College of Education for Women, 2019)
Were not experience Khalil Hawi capillary module as presented or routine in the format of the implications , but was saturated transitions quality that targeted built by visionary and mechanisms expressive , Valgosaidp when the container is a clash between two worlds world Nahdi to promote world on the ashes , and often strained poet himself to achieve an approach between worlds , and in the midst of those caesarean section exhausted poet in touch his tools and visions , and this is why the poetry Hawi toward westernization expressive as a result of the conflict concepts chronic , be sure to researcher not engaged in the overall qualitative changes in the structure and content, but the goal Acetknah level that qualitative transformation Visionary First , the nature of employment in the automated charging that transformation and enlightenment